Two-dimensional quasicrystals of decagonal order in one-component monolayer films - Comment - Schmiedeberg, Michael; Stark, Holger (Physical Review Letters, 2008)
A Comment on the Letter by A. Patrykiejew and S. Sokolowski, Phys. Rev. Lett. 99, 156101 (2007). The authors of the Letter offer a Reply.